ANALISIS PERBANDINGAN PENERAPAN GOOD CORPORATE GOVERNANCE SEBELUM DAN SESUDAH KONVERSI PADA BANK ACEH SYARIAH - Ranny Sharah; Musfiari Haridhi (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2020)
This study aims to see differences in the implementation of Good Corporate Governance in Bank Aceh Syariah before and after cut off. The type of this study is descriptive qualitative. The object of this study is Good Corporate Governance Bank Aceh Syariah. The type of data is secondary data as corporate annual reports of 2014-2017. The results of this study show that there was no significant difference in the implementation of Good Corporate Governance in Bank Aceh Syariah for the year of this research. The mechanism and tools for the effective implementation  of  Good  Corporate  Governance  are  relatively  the  same.  There  was  additional  organizational structure after cut off in the implementation of Good Corporate Governance with the establishment of a Sharia Supervisory Board, tasked with overseeing the business activities of the bank to fit the Fatwa of The National Sharia Council